EFEKTIVITAS PEMENUHAN HAK KONSELING DARI DINAS KESEHATAN KOTA PONTIANAK ATAS PERMOHONAN DISPENSASI KAWIN DI PENGADILAN AGAMA PONTIANAK KELAS I.A - NIM. A1011181023, SALLY (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Humans are social creatures, and marriage is one such interaction that binds a relationship to establish a new family (household). However, marriage is only permitted if the man and woman have reached the age of 19 (nineteen). Therefore, there are still deviations in underage marriages. Therefore, Law No. 1 of 1974 concerning Marriage provides a solution in the form of a marriage dispensation from the court. The Pontianak Class I.A Religious Court then collaborated with the Pontianak City Health Office in accordance with cooperation agreements no. W14-A1/1448/HM.01.1/VI/2022 and no. 800/11699/Dinkes-UA/2022. One of the requirements for submitting a marriage dispensation application is a Health Certificate from the Community Health Center, which is one of the factors that will determine the granting of the dispensation application. This includes counseling facilitated by the Pontianak City Health Office through the Community Health Center. The problem formulation in this study is